DECENTRALIZATION: AN INITIAL STUDY ON GOVERNANCE REFORMS TOWARDS THE WELFARE STATE - Budhy Prianto (Universitas Sebelas Maret, 2015)
Based on the constitution Indonesia is a state that adheres to the model welfare state. But in practice, the governance of the welfare state in Indonesia is merely a dream. This when seen from the facts of the neglect of issues of fundamental rights of citizens, such as the high number of poor people, the number of maternal and child mortality, school dropout rate, and so on. Centralization is a major obstacle of weak governance in realizing this welfare state. Therefore this article attempts to offer a thought for the reform of the welfare state governance through decentralization. Keywords: decentralization; governance; state; reform; welfare state